2011
DOI: 10.5172/conu.2011.39.1.106
|View full text |Cite
|
Sign up to set email alerts
|

Quality of work life and productivity among Iranian nurses

Abstract: Nurses are amongst the employees whose lives are fully affected by the quality of work life (QWL) as a consequence of dynamic changes in work environment. Excessive workload and poor work conditions are focal issues in nursing. The QWL assessment is an important and basic effort to deal with this issue. Moreover, staff productivity is a worthy goal of organizations tending to grow. If the relationship between the QWL and productivity becomes apparent, managers can provide conditions for promoting the QWL for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
89
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 43 publications
9
89
2
1
Order By: Relevance
“…The results showed that job promotion, job security, job proud, participation, management support and pay and benefit were key factors in nurses' quality of working life. These findings are consistent with other similar studies that found moderate to low levels of nurses' QWL because of increased workload, poor staffing, insufficient pay, lack of professional development opportunities, job insecurity, inappropriate working environment and lack of facilities (Almalki et al, 2012;Boonrod, 2009;Nayeri et al, 2011;Rastegari et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results showed that job promotion, job security, job proud, participation, management support and pay and benefit were key factors in nurses' quality of working life. These findings are consistent with other similar studies that found moderate to low levels of nurses' QWL because of increased workload, poor staffing, insufficient pay, lack of professional development opportunities, job insecurity, inappropriate working environment and lack of facilities (Almalki et al, 2012;Boonrod, 2009;Nayeri et al, 2011;Rastegari et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Improving employees' QWL is a prerequisite to increase their organisational productivity (Dolan et al, 2008;Bragard et al, 2012;Nayeri et al, 2011). High QWL organisations achieve better productivity and become highly competitive.…”
Section: Introductionmentioning
confidence: 99%
“…Nayak et al also found the positive effects of QWL on organizational effectiveness and healthcare quality (12). Moreover, DehghanNayeri et al and Salamzadeh et al found a positive relationship between nurses' QWL and their productivity (13), denoting that higher QWL is associated with higher organizational productivity. Good working conditions are a prerequisite to staff empowerment (3) and empowered staff can positively affect organizational outcomes and effectiveness.…”
Section: Discussionmentioning
confidence: 97%
“…Quality of work life is a multidimensional concept making it very complicated to explore (Dehghan Nayeri et al, 2011;Rathi, 2009;Tatawar & Nambudiri, 2014). It means removing the undesirable behavior and adding or modifying the working conditions in order to gain the desirable behavior and a favorable environment (Islam, 2012).…”
Section: Quality Of Life As a Multi-dimensional Conceptmentioning
confidence: 99%